A police education programme to integrate occupational safety and HIV prevention: protocol for a modified stepped-wedge study design with parallel prospective cohorts to assess behavioural outcomes. Issue 8 (10th August 2015) - Strathdee, Steffanie A; Arredondo, Jaime; Rocha, Teresita; Abramovitz, Daniela; Rolon, Maria Luisa; Patiño Mandujano, Efrain; Rangel, Maria Gudelia; Olivarria, Horcasitas Omar; Gaines, Tommi; Patterson, Thomas L; Beletsky, Leo
Abstract : Introduction: Policing practices are key drivers of HIV among people who inject drugs (PWID). This paper describes the protocol for the first study to prospectively examine the impact of a police education programme (PEP) to align law enforcement and HIV prevention. PEPs incorporating HIV prevention (including harm reduction programmes like syringe exchange) have been successfully piloted in several countries but were limited to brief pre–post assessments; the impact of PEPs on policing behaviours and occupational safety is unknown. Objectives: Proyecto ESCUDO (SHIELD) aims to evaluate the efficacy of the PEP on uptake of occupational safety procedures, as assessed through the incidence of needle stick injuries (NSIs) (primary outcome) and changes in knowledge of transmission, prevention and treatment of HIV and viral hepatitis; attitudes towards PWID, adverse behaviours that interfere with HIV prevention and protective behaviours (secondary outcomes). Methods/analysis: ESCUDO is a hybrid type I design that simultaneously tests an intervention and an implementation strategy. Using a modified stepped-wedge design involving all active duty street-level police officers in Tijuana (N=∼1200), we will administer one 3 h PEP course to groups of 20–50 officers until the entire force is trained. NSI incidence and geocoded arrest data will be assessed from department-wide de-identified data. Of the consenting police officers, a subcohort (N=500) will be randomly sampled from each class to undergo pre-PEP and post-PEP surveys with a semiannual follow-up for 2 years to assess self-reported NSIs, attitudes and behaviour changes. The impact on PWIDs will be externally validated through a parallel cohort of Tijuana PWIDs. Ethics/dissemination: Research ethics approval was obtained from the USA and Mexico. Findings will be disseminated through open access to protocol materials through the Law Enforcement and HIV Network. Trial registration number: NCT02444403.